Preparation and performance of electrically conductive Nb-doped TiO2/polyaniline bilayer coating for 316L stainless steel bipolar plates of proton-exchange membrane fuel cells. Issue 35 (25th May 2018) - Wang, Yanli; Zhang, Shenghua; Lu, Zhaoxia; Wang, Ping; Ji, Xiaohong; Li, Weihua
Abstract : A bilayer coating composed of an inner layer of Nb-doped TiO2 and an external polyaniline layer with small SO4 2− groups was prepared; the bilayer coating could protect 316L more effectively from the penetration of corrosive ions. Abstract : A bilayer coating composed of an inner layer of Nb-doped TiO2 obtained by the sol–gel method and an external polyaniline layer with small SO4 2− groups obtained by galvanostatic deposition was prepared to protect 316L stainless steel bipolar plates of proton-exchange membrane fuel cells. The corrosion resistances of bare 316L and 316L with single polyaniline coating and Nb-doped TiO2 /polyaniline bilayer coating were investigated. The experimental results indicated that both single and bilayer coatings increased the corrosion potential and decreased the corrosion current density compared with bare 316L stainless steel. A thirty-day exposure experiment indicated that the Nb-doped TiO2 /polyaniline bilayer showed high stability, and it protected 316L more effectively from the penetration of the corrosive ions.